PENGARUH FISIOTERAPI DADA TERHADAP POLA DAN FREKUENSI NAFAS PADA PASIEN TUBERKULOSIS DI PUSKESMAS SIBANDE - Berutu, Suryani; Nurhabibi Berutu; Subki Ramadhan; Elis Anggeria; Devi Ardila (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
Tuberculosis (TB) is a disease that causes many problems in the lungs, and the bacteria that cause this disease are bacteria (Mycobacterium tuberculosis). TB has several typical symptoms with the main symptoms such as experiencing a cough that produces phlegm or does not produce phlegm. Therefore, non-medical therapy can be used to treat and help expel phlegm, namely chest physiotherapy. The aim of this study was to determine the effect of chest physiotherapy on breathing patterns and frequency. The research method is a quasi-experimental design using a single group pretest-posttest design. The population in this study was 22 people suffering from TB. The sampling technique was saturated sampling, and the sample size was 22 people. Analysis of this research data uses a non-parametric test, namely the Wilcoxon test. The research results obtained a significant value of 0.000<0.005 indicating the influence of chest physiotherapy on respiratory frequency. Furthermore, a significant value of 0.002 <0.005 indicates the influence of chest physiotherapy on breathing patterns. The results of this study can be concluded that chest physiotherapy has an influence on breathing patterns and frequency in TB patients.